IMAN DENGAN AKAL DAN ETIKA MENURUT THOMAS AQUINAS - Andri Fransiskus Gultom (Bahasa Indonesia, 2018)
One of very famous figure in Western philosophy in the scholastic era was Thomas Aquinas. The teachings of Thomas a debate in the Western world that is still influenced by the teachings of Augustine influenced by Neoplatonism. According toAquinas that we ought to balance reason and faith, her sense helped build the foundations of Christian philosophy. However, it is important to realize that it is not always possible due to limited sense. Intellect can not give an explanation of life again (resurrection). For the limitations of the intellect can not be able to find the source of that knowledge. For that reason alone will not be able to prove the essential reality of the Christian faith. Therefore, he found Christian dogma was exactly as described in the words of the Lord. Thomas outlook regarding the recognition of God proved by using human reason. Ratio or human reason can know that God exists, and also some of the attributes of God. Thomas put forward a five-way prove that God does exist.